Perception of lecturers and students on entrepreneurship education on venture creation: the case of Gweru Polytechnic College, Zimbabwe - MABHANDA, WILSON (IJRDO - Journal of Applied Management Science, 2016)
Entrepreneurship education has emerged as an instrument for poverty alleviation, by way of providing opportunities and avenues of career options and choices even to graduates of polytechnic education. The purpose of this study is to explore the perception of students towards entrepreneurship education in influencing venture creation after their tertiary education. The researcher employed a case study method approach where data was collected through focus group discussions, open-ended questionnaires and face to face interviews. Purposive sampling was employed to collect data for this study. Data were thematically analysed in line with the qualitative research approaches. It emerged from empirical findings of this study that both lecturers and students share similar views that Entrepreneurship Skills Development (ESD) is a welcome additional curriculum because it has the potential to boost students’ motivation to create their own ventures after school. The study findings highlighted inadequate content, lack of depth, less time allocated for the subject and otherwise lecturers who teach it are very qualified but not in entrepreneurship as a discipline. This study recommends that ESD curriculum be enriched and students be given option to take up as a discipline to Higher National Diploma in Entrepreneurship. Furthermore, expert lecturers are to be recruited to teach entrepreneurship education in polytechnic colleges in Zimbabwe. The government of Zimbabwe must take a robust intervention to assist new venture creation across the country in order to mitigate poverty by employing home grown solutions sustained by Zimbabwe Agenda for Sustainable Socio- Economic Transformation ( ZIMASSET).